2016
DOI: 10.1016/j.jag.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pattern of potential woody cover in Texas savanna

Abstract: While woody plant encroachment has been observed worldwide in savannas and adversely affected the ecosystem structure and function, a thorough understanding of the nature of this phenomenon is urgently required for savanna management and restoration. Among others, potential woody cover (the maximum realizable woody cover that a given site can support), especially its variation over environment has huge implication on the encroachment management in particular, and on tree-grass interactions in general. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
(49 reference statements)
2
17
0
Order By: Relevance
“…Our results generally agree with the observation that the rainfall gradient of the Kalahari is associated with an increase in woody vegetation [16][17][18][19][20]. Interestingly, the highest species richness was recorded at Kuke (Figure 1-Site 7), where the annual precipitation is 450 mm (in the middle of the rainfall gradient).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results generally agree with the observation that the rainfall gradient of the Kalahari is associated with an increase in woody vegetation [16][17][18][19][20]. Interestingly, the highest species richness was recorded at Kuke (Figure 1-Site 7), where the annual precipitation is 450 mm (in the middle of the rainfall gradient).…”
Section: Discussionsupporting
confidence: 91%
“…Rainfall affects water availability, and this factor has been described as the most important determinant describing woody vegetation communities, particularly as it limits the amount of primary productivity within an area [16][17][18][19][20]. For example, in a continental study of African savannas, Sankaran et al [16] identified that woody cover increased linearly with mean annual precipitation (MAP) above 150 mm until maximum woody cover was reached at 650 mm.…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they are anticipated to be among the ecosystems most sensitive to future land use and climate changes [9,10], and it is important to gain a mechanistic understanding of 2 of 17 their vegetation-atmosphere exchange. While the woody cover in savannas, e.g., tree cover, adversely affect ecosystem structures and functions, an intensive understanding of woody cover is required for savanna conservation and management [11]. Woody cover growth is related to available water, climate, human activities [12], and herbivory level [11] in the form of porosity, leaf area index (LAI), and clumping index (CI).…”
Section: Introductionmentioning
confidence: 99%
“…While the woody cover in savannas, e.g., tree cover, adversely affect ecosystem structures and functions, an intensive understanding of woody cover is required for savanna conservation and management [11]. Woody cover growth is related to available water, climate, human activities [12], and herbivory level [11] in the form of porosity, leaf area index (LAI), and clumping index (CI). Savannas are spatially heterogeneous, open ecosystems, and the canopy openness presents a challenge for evaluating canopy LAI and other biophysical parameters, since most remotely sensed methods were developed for ideal and closed canopies [13,14].…”
Section: Introductionmentioning
confidence: 99%